Efeito pró-cicatrizante do triterpeno 3β,6β,16β-Trihydroxylup-20(29)-ENE (CLF-1) isolado de folhas de Combretum leprosum e atividade antitumoral de uma lectina isolada da esponja marinha Haliclona caerulea - Nascimento Neto, Luiz Gonzaga do (2016)
The number of cases of morbidity and mortality in patients with chronic wounds has increasing every year. In this sense, wound healing has become one the major dermatological problems. Secondary metabolites from plants have been used in several assays as promising molecules on various diseases attracted importance on treatment of various diseases. However, there are few data about it effect on wound healing. Combretum leprosum Mart. is a native species of the Caatinga and its ethanolic extract is commonly used as a healing agent, as a sedative and treatment of haemorrhages. A of the aim of the study was to evaluate the effect of triterpene 3β, 6β, 16β-trihydroxylup-20(29)-ene (CLF-1) isolated from ethanolic extract from the leaves of Combretum leprosum on skin wounds induced in vitro and in vivo lesions was avaluated. In vitro assay, the CLF-1 (2.5 μg/mL) not showed toxicity to human dermal fibroblasts (HDF). Moreover, the CLF-1 induced fibroblasts migration to the healing of the artificial injury with most effectiveness than control at 24h. In addition, the molecular mechanism of the CLF-1 treatment was studied. The results suggest that migration of fibroblasts occurs by upregulated expression of TGF-β1 and reduced levels of the inflammatory cytokine TNF-α. In the in vivo study, experimental skin lesions were created in the back of mice and treatment with the ethanolic extract from C. leprosum (EECL) and CLF-1 was evaluated for 12 days. The treatment with EECL and CLF-1 induced a faster and more effective epithelialization when compared to control. The histopathological assessment showed that EECL and CLF-1 has similar profiles during the regenerative process. This result suggest that probably the active component in the EECL may be CLF-1. Beyond of the spend about the wound healing chronic diseases as cancer are estimated as one of the main causes of dead and one of the main spending factors to the health systems. The conventional treatments, such as surgery, chemotherapy and radio are effective against primary tumors, hence not have the same effect in the later stages of the disease. In this sense, several biomolecules has attracted interest from the researchers because its antitumor potential. Marine sponjes are a biological reservoir of biomolecules, especially lectins. Lectins are proteins that bind reversibel way to carbohydrate epitops without modified them. Unlike plant lectins, there are few reports describing the mechanism of action of lectins from marine sponges to induce apoptosis in tumor cells. The effect of a lectin isolated from the marine sponge Haliclona caerulea (H3) on human breast cancer MCF-7 cell line was evaluated. H3 caused MCF7 cell reduction of viability in more than 50% (IC50=100 μg/ml) at 6h, 24h and 48h. However, on normal cells, the treatment with H3 induced a reduction in over 50% only at the highest dose tested (500 μg/ml). Furthermore, H3 provoke arrest in the G1 cell cycle phase and induce MCF7 cells apoptosis in 24h and 48h. Lysotracker Red and real-time qPCR assays suggest that effect of H3 may be related to a dynamic balance between apoptosis and autophagic cell death mediated by increase of expression of caspase-9 and LC3. In conclusion, the results suggest that CLF-1 and H3 lectin may be promising biomolecules to treatment of acute and chronic wounds and rare diseases like cancers.